EFFECTIVENESS OF NON-CASH MOTOR VEHICLE TAX PAYMENTS AT REGIONAL TECHNICAL SERVICE UNITS (UPTD) AT THE BITUNG REGIONAL REVENUE AGENCY - Febrilly Indra Panelewen; Recky H. E. Sendouw; Meidy S. S. Kantohe (CV. Radja Publika, 2026)
The purpose of this study was to analyze the effectiveness of cashless Motor Vehicle Tax (PKB) payments at the Regional Technical Service Unit (UPTD) in Bitung. The method used was a descriptive qualitative approach, with data collected through interviews, observation, and documentation. Effectiveness was measured based on eight indicators: clarity of objectives, clarity of strategy, policy analysis process, thorough planning, appropriate program development, availability of infrastructure, effective and efficient implementation, and monitoring and control systems. The research results showed that seven indicators were met: taxpayers understood the policy's objectives and strategies, planning and programs were well-developed, digital infrastructure was adequate, and the monitoring system was running periodically. However, one indicator, namely effective and efficient implementation, was not met due to ongoing challenges such as banking network disruptions and application errors . Therefore, the non-cash vehicle tax (PKB) payment policy at the Bitung Technical Implementation Unit (UPTD) was declared conceptually effective but technically suboptimal.